Manganese ferrite coated ZIF-8-wollastonite composite particle as well as preparation method and application thereof
By constructing a core-shell-shell structure of ZIF-8-wollastonite composite particles coated with manganese ferrite, the problems of difficult regeneration and poor stability of existing adsorbents in the treatment of heavy metal wastewater were solved, and efficient, stable removal and rapid separation of heavy metal ions were achieved.
Patent Information
- Application Number
- CN202511477704.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2026-01-23
AI Technical Summary
Existing adsorbents such as activated carbon, magnetic nanoparticles, and MOFs suffer from problems such as difficulty in regenerating adsorbent materials, agglomeration, and poor stability when treating heavy metal wastewater, which limits their practical application.
By using manganese ferrite-coated ZIF-8-wollastonite composite particles to construct a core-shell-shell structure, consisting of a manganese ferrite core, a ZIF-8 shell, and a wollastonite shell, combined with magnetic response properties and a rich porous structure, rapid separation and chemical stability can be achieved.
It improves adsorption efficiency, enhances the chemical stability and mechanical strength of the material, and achieves efficient removal and rapid separation of heavy metal ions, making it suitable for acidic or complex aquatic environments.
Smart Images

Figure CN121372355A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of core-shell structure composite materials, and in particular to a manganese ferrite coated ZIF-8-wollastonite composite particle, a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of heavy industry, the discharge of wastewater, waste gas and solid waste has increased significantly, among which wastewater pollution is particularly serious. Wastewater often contains heavy metal ions, which are difficult to degrade naturally and have strong toxicity even at very low concentrations. Therefore, how to efficiently treat heavy metal wastewater has become an urgent environmental problem to be solved. Currently commonly used adsorbents mainly include activated carbon, magnetic nanoparticles and metal organic framework materials (MOFs): On the one hand, activated carbon has the advantages of developed pore structure, simple preparation and strong adsorption, but has the problems of poor regeneration ability of adsorption materials and difficult solid-liquid separation, which limits its practical application. On the other hand, magnetic nanoparticles can effectively adsorb pollutants due to their high specific surface area, and can be quickly separated and reused under the action of an external magnetic field, which has good economy. However, due to the strong magnetic coupling between magnetic particles, they are prone to agglomeration, which significantly reduces the adsorption efficiency. In addition, MOFs materials have good effects in removing heavy metal ions and organic dyes due to their unique framework structure and high porosity. For example, ZIF-8 and ZIF-67 have been reported to have high removal rates. However, such materials are prone to hydrolysis in water and have poor stability in acidic wastewater conditions, and are difficult to recycle and utilize, which limits their engineering application. In summary, the existing activated carbon, magnetic nanomaterials and MOFs adsorbents all have defects that are difficult to overcome. Therefore, a manganese ferrite coated ZIF-8-wollastonite composite particle, a preparation method and application thereof are proposed. SUMMARY
[0003] Therefore, the present application provides a manganese ferrite coated ZIF-8-wollastonite composite particle, a preparation method and application thereof to solve or alleviate the technical problems in the prior art, and at least provide a beneficial choice.
[0004] The technical solution of the present application is as follows: a manganese ferrite coated ZIF-8-wollastonite composite particle, comprising a manganese ferrite core, a ZIF-8 shell layer coated on the outer surface of the manganese ferrite core, and a wollastonite shell layer further coated on the outer surface of the ZIF-8 shell layer, forming a three-layer structure of core-shell-shell.
[0005] The particle size of the manganese ferrite core is 10-100 nm, the thickness of the ZIF-8 shell layer is 20-200 nm, and the thickness of the wollastonite shell layer is 50-500 nm, which guarantees the integrity and dispersibility of the overall composite structure.
[0006] The mass percentage of the composite particle is 20-60% of manganese ferrite, 10-40% of wollastonite, and the specific surface area is 70-150 m² / g, the saturation magnetization is 70-85 emu / g, and the coercive force is 150-170 A / m, so that the composite particle has strong adsorption capacity and good magnetic response performance.
[0007] The application also provides a preparation method of manganese ferrite coated ZIF-8-wollastonite composite particles, which comprises the following steps: S1: manganese ferrite nanoparticle synthesis and carboxyl modification: dissolve in ethylene glycol, stir to form a uniform solution, then add hexamethyltetramine and a polymer stabilizer, stir until completely dissolved, transfer to a stainless steel reaction kettle, react at 150-170 DEG C for 6h, collect the precipitate after cooling, wash, dry and calcine at 480-520 DEG C under nitrogen atmosphere for 2-4h to obtain manganese ferrite nanoparticles; the manganese ferrite nanoparticles are reacted with a silane coupling agent and succinic anhydride to obtain carboxyl surface modified manganese ferrite nanoparticles; S2: manganese ferrite coated ZIF-8 composite particle synthesis: disperse the carboxyl modified manganese ferrite nanoparticles in a methanol solution containing 2-methyl imidazole and a surfactant, ultrasonically disperse for 10 min, then add a methanol solution, and self-assemble in a 60±5 DEG C water bath under the action of a magnetic stirrer for 10-14h, finally separate the product by a magnet and wash with methanol to obtain manganese ferrite coated ZIF-8 composite particles; S3: manganese ferrite coated ZIF-8-wollastonite composite particle synthesis: disperse the manganese ferrite coated ZIF-8 composite particles in deionized water, ultrasonically disperse for 30 min, add an ammonia solution, stir to form solution 1; dissolve tetraethyl orthosilicate in ethanol, add a surfactant and deionized water to stir to form solution 2; mix solution 1 and solution 2 to react and age for 1-4h to form a gel state, then calcine in a tube furnace at 380-420 DEG C under nitrogen atmosphere for 2-6h, grind and crush to obtain manganese ferrite coated ZIF-8-wollastonite composite particles.
[0008] Further preferably, in S1 The mass ratio of manganese ferrite, ethylene glycol and polyvinylpyrrolidone is 1-100:1-100:1-500.
[0009] Further preferably, the polymer stabilizer is one or more of polyethylene glycol, dextran, polyvinylpyrrolidone, fatty acid, polyvinyl alcohol, polypeptide, gelatin, chitosan, methylsilane, and liposome, and the mass ratio of the polymer stabilizer to manganese ferrite is 1-10:1-1000.
[0010] Further preferably, the silane coupling agent in S1 is one or more of vinyltrichlorosilane, vinyltriethoxysilane, anilinomethyltrimethoxysilane, anilinomethyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and the mass ratio of the silane coupling agent to manganese ferrite is 1:1-50. Further preferably, the surfactant in S2 is one or more of lauryl alcohol chloride, aromatic alkyl oxyether, isopentylenyl hydroxyphenyl ether, polyethylene glycol sulfate, and cetyltrimethylammonium bromide, and the mass ratio of the surfactant, 2-methylimidazole, and is 1-15:1-1000:1-1000.
[0011] Further preferably, the addition amount of in S3 is 20-50ml, and the mass ratio of tetraethyl orthosilicate to ethanol is 1-300:1-900.
[0012] The application also provides a use of the manganese ferrite coated ZIF-8-wollastonite composite particle for removing heavy metal ions in water, wherein the heavy metal ions are selected from at least one of and The application can achieve rapid separation and cyclic regeneration by using an external magnetic field, thereby greatly improving the service life of the adsorbent and the wastewater treatment efficiency.
[0013] The application has the following advantages due to the above technical solutions: The application forms a core-shell-shell composite structure by sequentially constructing a manganese ferrite core, a ZIF-8 shell, and a wollastonite shell, thereby forming a composite particle with complementary functions and stability. The manganese ferrite core endows the material with excellent magnetic response characteristics, so that the material can be rapidly and efficiently separated after adsorption by using an external magnetic field. The ZIF-8 shell provides abundant pores and active sites, acts as a main adsorption functional carrier, and uniformly embeds the manganese ferrite particles in the framework, thereby effectively reducing the strong magnetic coupling between the magnetic particles, reducing the agglomeration phenomenon, and improving the adsorption efficiency. Further, the wollastonite shell in the outermost layer plays a stabilizing and protecting role, avoids the hydrolysis instability of ZIF-8 in an acidic or complex water environment, significantly enhances the chemical stability and mechanical strength of the composite particle, and improves the application limitations of the current manganese ferrite adsorbent.
[0014] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Fig. 1 This is a production technology roadmap for manganese ferrite-coated ZIF-8-wollastonite composite particles according to the present invention. Fig. 2 This is a schematic diagram of the structure of the manganese ferrite-coated ZIF-8-wollastonite composite particles of the present invention. Detailed Implementation
[0017] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.
[0018] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0019] like Figs. 1-2 As shown, this embodiment of the invention provides a manganese ferrite-coated ZIF-8-wollastonite composite particle, comprising a manganese ferrite core, a ZIF-8 shell coating the outer surface of the manganese ferrite core, and a wollastonite shell coating the outer surface of the ZIF-8 shell. The composite particle has a core-shell-shell structure.
[0020] The manganese ferrite core has a particle size of 10–100 nm, the ZIF-8 shell thickness is 20–200 nm, and the wollastonite shell thickness is 50–500 nm; the mass percentage of the composite particles is 20–60% manganese ferrite, 10–50% ZIF-8, and 10–40% wollastonite, with a specific surface area of 70–150 m² / g, a saturation magnetization of 70–85 emu / g, and a coercivity of 150–170 A / m.
[0021] Example 1 S1: Synthesis and carboxylation modification of manganese ferrite nanoparticles Weigh out 3.8g each The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0022] The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0023] S2: Synthesis of manganese ferrite-coated ZIF-8 composite particles The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0024] S3: Synthesis of manganese ferrite-coated ZIF-8 / wollastonite composite particles The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0025] Example 2 S1: Synthesis of manganese ferrite nanoparticles and carboxyl modification The 4 g of vinyltrichlorosilane and 4 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0026] The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0027] S2: Synthesis of manganese ferrite-coated ZIF-8 composite particles The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0028] S3: Synthesis of manganese ferrite-coated ZIF-8 / wollastonite composite particles The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying.
[0029] Example 3 S1: Synthesis of manganese ferrite nanoparticles and carboxyl modification The 6 g of vinyltrichlorosilane and 6 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles modified with carboxyl groups were obtained by washing and drying. The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying.
[0030] The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying.
[0031] S2: Synthesis of manganese ferrite-coated ZIF-8 composite particles The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying. The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying.
[0032] S3: Synthesis of manganese ferrite-coated ZIF-8 / wollastonite composite particles The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying. The 10 g of vinyltrichlorosilane and 10 g of succinic anhydride were uniformly dispersed in 20 ml of dimethylformamide, stirred for 3 h, and then 15 g of the manganese ferrite particles dispersed in dimethylformamide by ultrasonic dispersion were added thereto, and stirring was continued for 3 h. After the reaction was completed, the manganese ferrite nanoparticles with a carboxyl surface were obtained by washing and drying.
[0033] Performance test: The manganese ferrite-coated ZIF-8 / wollastonite composite particles obtained in Examples 1 to 3 were subjected to a comprehensive performance test, and the test methods for various physical property parameters were as follows. Specific surface area test: The specific surface area and pore size analyzer was used, and the test was conducted in accordance with the standard GB / T19587-2004 "Determination of specific surface area of solid substances by gas adsorption BET method". Before the test, the sample was degassed under vacuum to ensure that the surface adsorption sites were fully exposed.
[0034] Magnetic performance testing: including saturation magnetization, coercivity and remanent magnetization, was conducted in accordance with GB / T38947-2020 "Methods for measuring magnetic properties of soft magnetic materials". The test was performed using a vibrating sample magnetometer (VSM) and the hysteresis loop of the sample was measured at room temperature.
[0035] False specific gravity test: The test is conducted in accordance with GB / T4511.1-2008 "General Rules for the Determination of False Specific Gravity of Chemical Products". A certain mass of sample is filled into a graduated cylinder, and the false specific gravity is calculated by the volume-mass ratio.
[0036] Ion adsorption performance testing: Referring to the laboratory static adsorption method, a simulated industrial wastewater system was constructed. The specific steps are as follows: Formulating and A mixed solution of four typical heavy metal ions was prepared, with the concentration adjusted to 2 mol / L, using deionized water as the solvent. Take 30 ml of simulated wastewater sample and add pre-weighed manganese ferrite-coated ZIF-8-wollastonite composite particle adsorbent under the conditions of no pH adjustment (keeping the solution in its natural state) and room temperature. Place the sample vial in a constant temperature shaker, take samples periodically, and separate the adsorbent from the solution by allowing it to stand. The absorbance of each heavy metal ion in the solution was measured using a UV-Vis spectrophotometer, the residual concentration at different time periods was calculated, and the removal rate was calculated accordingly.
[0037] Test Results and Analysis (1) Relationship between specific surface area and adsorption performance In Examples 1-3, succinic anhydride, 2-methylimidazole and With the increase in feed amount, the shell layer formed by ZIF-8 on the manganese ferrite surface gradually thickened, resulting in a gradual increase in the specific surface area of the composite particles from approximately 78 m² / g in Example 1 to approximately 85 m² / g in Example 3. This increase in specific surface area increased the number of active sites on the adsorbent surface, thereby enhancing its adsorption capacity. and The adsorption rates of heavy metal ions all showed a gradual increasing trend. Under the same adsorption conditions, Example 3 showed the best adsorption rate for heavy metal ions. The removal rate is close to 94%, which is significantly better than the approximately 85% in Example 1; Tables 1 to 3 below show the composite particle pairs prepared in Examples 1 to 3, respectively. and Adsorption rate test results of four heavy metal ions: Table 1: Adsorption rate of manganese ferrite coated ZIF-8-wollastonite composite particles on typical heavy metal ions (tested three times)
[0038] Table 2: Adsorption rate of manganese ferrite coated ZIF-8-wollastonite composite particles on typical heavy metal ions (tested three times)
[0039] Table 3: Adsorption rate of manganese ferrite coated ZIF-8-wollastonite composite particles on typical heavy metal ions (tested three times)
[0040] (2) Changes in magnetic properties With the increase of manganese ferrite content, the saturation magnetization of the composite particles gradually increases: the saturation magnetization of Example 1 is about 72 emu / g, and that of Example 3 reaches about 81 emu / g, which indicates that the response ability of the particles to the external magnetic field is enhanced, which is beneficial to the rapid recovery of the adsorbent after water treatment. At the same time, the coercivity and residual magnetization remain within a reasonable range, indicating that the material has good soft magnetic properties and will not have irreversible magnetization residues during magnetic separation.
[0041] The following Tables 4-6 show the specific surface area, saturation magnetization, coercivity, residual magnetization and apparent specific gravity of the composite particles obtained in Examples 1-3; Table 4: Technical indicators of manganese ferrite coated ZIF-8-wollastonite composite particles of Example 1 (tested three times)
[0042] Table 5: Technical indicators of manganese ferrite coated ZIF-8-wollastonite composite particles of Example 2 (tested three times)
[0043] Table 6: Technical indicators of manganese ferrite coated ZIF-8-wollastonite composite particles of Example 3 (tested three times)
[0044] (3) Stability of wollastonite shell Through long-term static adsorption experiments, it was found that the composite particles remained structural integrity in the solution range of pH = 3-9, and no obvious hydrolysis or collapse phenomenon occurred, which was due to the effective protection of the outermost wollastonite coating layer to ZIF-8, so that the composite particles could maintain adsorption capacity in acidic or complex wastewater environment for a long time.
[0045] (4) Comprehensive performance comparison Adsorption performance: Example 3 > Example 2 > Example 1; Magnetic response performance: the higher the manganese ferrite content, the greater the magnetization, which is beneficial to rapid separation; Stability: all three samples showed good water phase stability, but the sample with thicker wollastonite outer layer showed particularly good performance under acidic conditions; From the above performance tests, it can be seen that: By adjusting the feeding ratio of 2-methyl imidazole and , the growth degree of ZIF-8 on the surface of manganese ferrite can be effectively controlled, and then the specific surface area of the composite particles and the adsorption performance of heavy metal ions can be adjusted; The increase of manganese ferrite content significantly improves the saturation magnetization of the material, which enables it to achieve more efficient and rapid separation and recovery under the action of an external magnetic field; The protection of the wollastonite shell to ZIF-8 is significant, which ensures the chemical stability of the composite particles in acidic wastewater environment; The manganese ferrite coated ZIF-8-wollastonite composite particles prepared by the present application are superior to single manganese ferrite particles or ZIF-8 materials in terms of adsorption efficiency, magnetic recovery and structural stability, and have high engineering application value.
[0046] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto, any skilled person in the art can easily think of various changes or replacements within the technical range disclosed by the present application, which should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A manganese ferrite-coated ZIF-8-wollastonite composite particle, characterized by, The composite particle comprises a manganese ferrite core, a ZIF-8 shell layer coated on the outer surface of the manganese ferrite core, and a wollastonite shell layer further coated on the outer surface of the ZIF-8 shell layer, and the composite particle has a core-shell-shell structure.
2. The MnFe2O4-coated ZIF-8-wollastonite composite particles according to claim 1, characterized in that: The particle size of the manganese ferrite core is 10-100 nm, the thickness of the ZIF-8 shell layer is 20-200 nm, and the thickness of the wollastonite shell layer is 50-500 nm. 3.The manganese ferrite coated ZIF-8-wollastonite composite particle of claim 1, characterized in that: The mass percentage of the composite particle is manganese ferrite 20-60%, ZIF-8 10-50%, and wollastonite 10-40%, and the specific surface area of the composite particle is 70-150 m² / g, the saturation magnetization is 70-85 emu / g, and the coercive force is 150-170 A / m.
4. The method of producing a manganese ferrite coated ZIF-8-wollastonite composite particle according to any one of claims 1 to 3, characterized in that, The method comprises the following steps: S1: Synthesis and carboxylation modification of manganese ferrite nanoparticles: The manganese ferrite nanoparticles were dissolved in ethylene glycol and stirred to form a homogeneous solution. Hexamethylenetetramine and a polymer stabilizer were added and stirred until completely dissolved. The solution was then transferred to a stainless steel reactor and reacted at 150–170°C for 6 hours. After cooling, the precipitate was collected, washed, dried, and calcined at 480–520°C for 2–4 hours under a nitrogen atmosphere to obtain manganese ferrite nanoparticles. The manganese ferrite nanoparticles were then reacted with a silane coupling agent and succinic anhydride to obtain carboxyl-modified manganese ferrite nanoparticles. S2: Synthesis of MnFe2O4-coated ZIF-8 composite particles: Carboxyl-modified MnFe2O4nanoparticles were dispersed in a methanol solution containing 2-methylimidazole and a surfactant, and after ultrasonic dispersion for 10 min, a methanol solution of ZIF-8 was added Under the action of a magnetic stirrer, it was self-assembled in a 60±5°C water bath for 10-14 h, and finally the product was separated by a magnet and washed with methanol to obtain MnFe2O4-coated ZIF-8 composite particles; S3: synthesis of manganese ferrite coated ZIF-8-wollastonite composite particles: dispersing the manganese ferrite coated ZIF-8 composite particles in deionized water, ultrasonicating for 30 min, adding an ammonia solution, stirring to form solution 1; dissolving tetraethyl orthosilicate in ethanol, adding a surfactant and deionized water, and stirring to form solution 2; mixing solution 1 and solution 2 to react and aging for 1-4 h to form a gel state, and then calcining in a tube furnace under a nitrogen atmosphere at 380-420°C for 2-6 h, and grinding to obtain manganese ferrite coated ZIF-8-wollastonite composite particles.
5. The method of claim 4, wherein the method further comprises: 5 dispersing the ZIF-8-coated manganese ferrite particles in a solution of water and a dispersant; and 5 drying the ZIF-8-coated manganese ferrite particles. S1 with a mass ratio of 1 - 100 : 1 - 100 : 1 - 500.
6. The method of claim 4, wherein the method further comprises: 5 dispersing the ZIF-8-coated manganese ferrite particles in a solution of water and a dispersant; and 10 drying the ZIF-8-coated manganese ferrite particles. The polymer stabilizer is one or more of polyethylene glycol, dextran, polyvinylpyrrolidone, fatty acid, polyvinyl alcohol, polypeptide, gelatin, chitosan, methylsilane, and liposome, and the mass ratio of the polymer stabilizer to manganese ferrite is 1-10:1-1000.
7. The method of claim 4, wherein the method further comprises: 5 dispersing the ZIF-8-coated manganese ferrite particles in a solution of water and a dispersant; and 10 drying the ZIF-8-coated manganese ferrite particles. The silane coupling agent in S1 is one or more of vinyltrichlorosilane, vinyltriethoxysilane, anilinemethyltrimethoxysilane, anilinemethyltrimethoxysilane, and γ-aminopropyltriethoxysilane, and the mass ratio of the silane coupling agent to manganese ferrite is 1:1-50.
8. The method of claim 4, wherein the method is characterized by: The surfactant in S2 is selected from one or more of lauryl chloride alcohol, aromatic alkyl oxy ether, isopentylenyl hydroxy benzene ether, polyethylene glycol sulfate, or cetyl trimethyl ammonium bromide, and the mass ratio of surfactant, 2-methyl imidazole, and 1 - 15 : 1 - 1000 : 1 - 1000.
9. The method of claim 8, wherein the method further comprises: 5 dispersing the ZIF-8-coated manganese ferrite particles in a solution of water and a dispersant; and 10 drying the ZIF-8-coated manganese ferrite particles. The S3 in The amount of addition is 20-50 ml, and the mass ratio of tetraethyl orthosilicate to ethanol is 1-300:1-900.
10. Use of a manganese ferrite coated ZIF-8-wollastonite composite particle according to any one of claims 4-9, characterized in that: For removing heavy metal ions in water bodies, the heavy metal ions are selected from at least one of and , and can be quickly separated and recycled by an applied magnetic field.